PSYCHOLOGICAL CHARACTERISTICS OF THE CURRENT DEVELOPMENT OF MISCHIEVOUSNESS AS A COMPONENT OF PLAY COMPETENCE (BASED ON THE RESULTS OF A DIAGNOSTIC EXPERIMENT) - Gordiienko-Mytrofanova, Iya; Bezkorovainyi , Serhii (PSYCHOLOGICAL JOURNAL, 2024)
The article presents an empirical study focused on the psychological characteristics of the development of mischiefness as a component of playfulness/ludic competence. The sample for the baseline study consisted of 238 individuals aged 21 to 40. A significant correlation between mischiefness and the overall level of playfulness (0.658) highlights its central role in the structure of this phenomenon. Mischiefness is also associated with the ability to manage the emotions of others (0.395), which indicates the capacity of such individuals to influence the emotional state of those around them, especially in situations where there is a risk of violating social norms. The correlation with self-sustaining humor (0.343) underscores their ability to maintain a positive outlook on life, remaining optimistic even in difficult situations; creating an atmosphere of ease and relaxation, which reduces social tension and sustains the dynamics of interaction. The correlation with tolerance for uncertainty (0.264) reflects their ability to flexibly adapt to unpredictable circumstances, using them as opportunities for growth. Openness to new experiences (0.225) emphasizes their inclination toward creativity and experimentation. The correlation with identification in empathy (0.216) underscores their ability to feel and understand the emotions of others, allowing them to skillfully manage social interactions. Moderate extraversion (0.234) fosters active social engagement, while caution in seeking new experiences (0.162) helps them avoid unnecessary risks, balancing social activity with restraint. The results fully confirm the findings of theoretical, methodological, and empirical studies, providing the most comprehensive description of the psychological content of the play position "Frolicsome Fellow." Mischiefness is a complex and multifaceted phenomenon characterized by the ability to direct the attention of others through the creation of "self-testing" situations; the ability to navigate between social norms and taboos through flexibility and emotional sensitivity, while maintaining emotional stability; and free creative self-expression through playful antics, flirtation, and provocative actions, integrating playful elements into interpersonal interactions.